Enhancing Soil Health: Nanotechnologies for Effective Remediation and Sustainable Development - Kho, Brendan Lik Sen; Hua, Ang Kean; Mohd Fadzil Ali, Ahmad (Tecno Scientifica, 2024)
The growing population has led to the increase in contamination to the soil, affecting the soil environment which indirectly affects importance of human health. Soil remediation is important to remove and reduce the level of contamination in the soil medium. If the contaminants present in the soil is not remediated, the possibilities of it to spread will increase due to the presence of water flow inside the soil medium, further contaminating soils that are previously clean. Hence, several nanotechnologies and nanomaterials were discovered by researchers, allowing the remediation of soil that are contaminated by different pollutants to be effectively carried out. The nanotechnologies and nanomaterials discussed in this paper involves physical, chemical and biological type of remediation. It is being known that nanoscale remediation can have higher effectiveness compared to microscale remediation. Most of the discussed nanotechnologies requires longer period of time but the effectiveness in the removal or reduction of contaminants are very high. Remediation of contaminated soils allow more land to be available for human development and exploitation. Humans are urged to reduce the chances of contamination activities or accident as contamination to the soil can adversely affect the local environment and the human health.